Increasing nitrogen absorption and assimilation ability under mixed NO3− and NH4+ supply is a driver to promote growth of maize seedlings - Peng WANG; Cheng-dong WANG; Xiao-lin WANG; Yuan-hua WU; Yan ZHANG; Yan-guo SUN; Yi SHI; Guo-hua MI (Journal of Integrative Agriculture, 2023)
Compared with sole nitrate (NO3−) or sole ammonium (NH4+) supply, mixed nitrogen (N) supply may promote growth of maize seedlings. Previous study suggested that mixed N supply not only increased photosynthesis rate, but also enhanced leaf growth by increasing auxin synthesis to build a large sink for C and N utilization. However, whether this process depends on N absorption is unknown. Here, maize seedlings were grown hydroponically with three N forms (NO3− only, 75/25 NO3−/NH4+ and NH4+ only). The study results suggested that maize growth rate and N content of shoots under mixed N supply was little different to that under sole NO3− supply at 0–3 d, but was higher than under sole NO3− supply at 6–9 d. 15N influx rate under mixed N supply was greater than under sole NO3− or NH4+ supply at 6–9 d, although NO3− and NH4+ influx under mixed N supply were reduced compared to sole NO3− and NH4+ supply, respectively. qRT-PCR determination suggested that the increased N absorption under mixed N supply may be related to the higher expression of NO3− transporters in roots, such as ZmNRT1.1A, ZmNRT1.1B, ZmNRT1.1C, ZmNRT1.2 and ZmNRT1.3, or NH4+ absorption transporters, such as ZmAMT1.1A, especially the latter. Furthermore, plants had higher nitrate reductase (NR) glutamine synthase (GS) activity and amino acid content under mixed N supply than when under sole NO3− supply. The experiments with inhibitors of NR reductase and GS synthase further confirmed that N assimilation ability under mixed N supply was necessary to promote maize growth, especially for the reduction of NO3− by NR reductase. This research suggested that the increased processes of NO3− and NH4+ assimilation by improving N-absorption ability of roots under mixed N supply may be the main driving force to increase maize growth.